Long-Term Followup Comparing Two Treatment Dosing Strategies of 125I Plaque Radiotherapy in the Management of Small/Medium Posterior Uveal Melanoma - Timothy G. Murray; Arnold M. Markoe; Aaron S. Gold; Fiona Ehlies; Ernesto Bermudez; Andrea Wildner; Azeema Latiff (Journal of Ophthalmology)
Objective. To investigate the efficacy of two different dosing strategies of radioactive iodine-125 (125I) in the management of small- and medium-sized posterior uveal melanoma. Patients and Methods. The medical records of consecutive patients with choroidal melanomas between 1.5 and 5.0 mm in apical height treated initially with 125I plaque radiotherapy were reviewed. Patients were treated with one of the following two treatment dosing strategies: (1) 85 Gy to the apical height of the tumor (group 1) or (2) 85 Gy to a prescription point of 5.0 mm (group 2). Results. Of 95 patients, 55 patients were treated to the apical height of the tumor, and 40 were treated to a prescription point of 5.0 mm. Comparative analysis of the incidence rates of specific complications between the two groups demonstrates that group 2 had a significantly higher incidence of radiation retinopathy, radiation optic neuropathy, and/or visually significant cataract formation than group 1 (). Conclusion. Treatment of choroidal melanomas less than 5 mm in apical height with 125I brachytherapy to the true apical height is equally effective when compared to treatment with 85 Gy to 5.0 mm. Treatment to the apical height of the tumor may result in lower incidence of radiation-related complications.